2014
DOI: 10.3171/2014.7.spine13564
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal oblique corridor to the L2–S1 intervertebral discs in the lateral position: an anatomic study

Abstract: Object Access to the intervertebral discs from L2–S1 in one surgical position can be challenging. The transpsoas minimally invasive surgical (MIS) approach is preferred by many surgeons, but this approach poses potential risk to neural structures of the lumbar plexus as they course through the psoas. The lumbar plexus and iliac crest often restrict the L4–5 disc access, and the L5–S1 level has not been a viable option from a direct lateral approach. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
148
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(159 citation statements)
references
References 32 publications
(53 reference statements)
6
148
2
3
Order By: Relevance
“…However, numerous studies have shown neurologic injury resulting from this transpsoas approach, which is in close anatomic proximity to the lumbar nerve plexus [2,16,18,25,26]. The oblique anterolateral retroperitoneal approach to the lumbar spine passes anterior to the psoas muscle and lateral to the abdominal vessels [11]. We found that the access through this anatomically predefined pathway was associated with a low risk of vascular and neurologic complications in a large cohort at a single center.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, numerous studies have shown neurologic injury resulting from this transpsoas approach, which is in close anatomic proximity to the lumbar nerve plexus [2,16,18,25,26]. The oblique anterolateral retroperitoneal approach to the lumbar spine passes anterior to the psoas muscle and lateral to the abdominal vessels [11]. We found that the access through this anatomically predefined pathway was associated with a low risk of vascular and neurologic complications in a large cohort at a single center.…”
Section: Discussionmentioning
confidence: 70%
“…Davis et al [11], in a cadaveric study, described the retroperitoneal oblique corridor to the L2 to S1 intervertebral discs. They concluded that use of this oblique corridor, anterior to the psoas muscle, may avoid many of the anatomic structure-associated complications with the anterior or transpsoas approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This finding indicates that the more anterior the cage position, the more lordosis will be achieved. The amount of lordosis achieved can also depend on the approach to the spine, e.g., an oblique anteroposterior trajectory via the vacant oblique corridor in front of the psoas muscle 20) in OLIF or a direct lateral to lateral-anterior trajectory in XLIF 21) . These differences can also lead to an anterior longitudinal ligament (ALL) tear or injury, as XLIF can cause this complication when the cage is placed anteriorly because of its trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric investigations by Davis et al (28) and Molinares et al (29) demonstrate an adequately sized, left-sided oblique corridor at L2-L5, which could be widened via lateral decubitus positioning and the use of approach retractor systems. The prior study (28) reported left oblique corridor sizes for L2/L3, L3/L4, L4/L5 whilst the latter (29) reported measurements of these levels in addition to L1/L2 and L2/L3. Both studies were consistent in demonstrating that the larger corridors were available in the upper lumbar levels, and has been attributed to the conical morphology of the psoas muscle.…”
Section: Discussionmentioning
confidence: 99%